An Investigation Into the Lexical-Semantic Meanings of Causative Verbs in English - Ravshanjonovna, Karimjonova Shahlo (Jurnal Multidisiplin Madani, 2024)
This scientific article explores the lexical-semantic nuances of causative verbs in the English language. Causative verbs play a crucial role in expressing the relationships between actions and their agents, impacting the meaning and interpretation of various linguistic constructs